Evaluating the Economic Impact of Diabetes Mellitus: A Hospital-Centric Cost Analysis in Hail, Saudi Arabia - Alshammari AM; Elnaem MH; Ong SC (ClinicoEconomics and Outcomes Research)
Abdullah Mohammad Alshammari,1,2 Mohamed Hassan Elnaem,3 Siew Chin Ong1 1School of Pharmaceutical Sciences, Universiti Sains Malaysia, Penang, Malaysia; 2Hail Health Cluster, Hail, Saudi Arabia; 3University of Ulster, Coleraine, Northern Ireland, UKCorrespondence: Siew Chin Ong, Discipline of Social and Administrative Pharmacy, School of Pharmaceutical Sciences, Universiti Sains Malaysia, Penang, Malaysia, Email siewchinong@usm.myBackground: Diabetes mellitus (DM) is a chronic non-communicable disease (NCD) that imposes a significant economic burden on healthcare systems and households. This study aimed to estimate the direct medical costs associated with diabetes care from a hospital perspective in Hail, Saudi Arabia.Methods: A retrospective, hospital-based study was conducted using data from hospital records of diabetic patients treated at King Khalid Hospital (KKH) and King Salman Specialized Hospital (KSSH) in Hail. The study employed a top-down approach to estimate direct medical costs, including consultation, lab tests, medications, admissions, and annual check-ups. Costs were adjusted to US dollars (1 USD = 3.75 SAR). Ethical approval was obtained from the Hail Health Cluster (IRB Log Number: 2023– 44).Results: A total of 377 diabetic patients were included in the study. The mean age was 58.02 years (SD = 18.80), with 53.3% male and 46.7% female patients. The average total annual cost per patient was US$6689.1 (± 3450.1), with admission costs being the highest contributor (US$2686.0 ± 3373.0). The total estimated cost for all patients combined was approximately US$2.52 million. Older age, female gender, DM complications, and treatment at KSSH were significantly associated with higher direct costs.Conclusion: The economic burden of diabetes is substantial and continues to rise annually. Policymakers should prioritize cost-effective interventions and improve data collection across hospitals to better understand and mitigate the financial impact of diabetes.Keywords: diabetes mellitus, economic burden, direct medical costs, Saudi Arabia, hospital perspective